Influence of Public Works Officers on Quality of Public Building Projects Undertaken by Devolved Units: A Case Study of Public Building Projects in Busia County - Wamalwa , C. Mukoche (African Journal of Education,Science and Technology (AJEST), 2018)
The construction sector is a key player for sustainable development. Both levels of government in Kenya (National and County) have identified construction sector as a driver of the development agenda. The devolved units (counties and constituencies) have invested quite substantial amount of public funds in infrastructure development and yet social audit and media reports have raised the concern over poor quality of the projects undertaken by these devolved units. This study therefore sought to investigate the roles played by the public works officers as the consultants for public building projects. A case study involving sixty four projects randomly sampled from Busia County and its seven constituencies was carried out. Eight projects were randomly sampled from County projects and each of the seven constituencies giving a total of sixty four projects involved in the study. The study was a sample survey whose data was collected using questionnaires, interview schedules and physical observation exercise. The data was analyzed using descriptive statistics and Chi-square good-for-fit tests. The findings indicated very low participation of the public works officers in the construction process of the public building projects undertaken by devolved units. The participation rate was at 15% which implied that the projects were constructed without proper design, supervision and technical input by the consultants. The physical observation assessment revealed quality of the public building projects stood at 34% compliance to building specifications and standards which is inadequate to meet required standards. It is concluded that the involvement of public works officers in the construction management process of public building projects undertaken by the devolved units is inadequate and impacts negatively on quality of the projects. In order to achieve the sustainable development as far as the infrastructural development is concerned, more involvement of consultants in construction process will be critical. This therefore calls for development of the legal and quality frameworks to guide the construction sector at the devolved units.